A single-chip tuner for DVB-T. - Dawkins, M.
A new architecture is presented for a single-chip tuner for digital terrestrial television, based on existing double conversion and direct conversion topologies. The new design forms part of a mixed-signal Digital Video Broadcasting-Terrestrial (DVB-T) receiver system, employing digital signal processing at baseband to ensure minimal performance requirements for the analog circuitry. To evaluate the potential performance of this new tuner/receiver system, high-level system simulations have been performed, followed by the construction of a prototype DVB-T receiver using a custom-designed analog ASIC which integrates all analog tuner blocks (including channel filtering) on one chip. Measured results from this chip, implemented in a 20-GHz bipolar technology, show an overall third-order input referred intercept point of 116 dBμV, a noise figure of 14 dB and an automatic gain control range of 71.4 dB, drawing 250 mA at a 5-V supply.
Keywords: 14 dB; 20 GHz; 250 mA; 5 V; DVB-T.; Automatic gain control; Channel filtering; Custom-designed analog ASIC; Digital signal processing; Digital terrestrial television; Direct conversion; Double conversion; High-level system simulations; Mixed-signal Digital Video Broadcasting-Terrestrial receiver system; Noise figure; Single-chip tuner; Third-order input referred intercept point